Solid state battery
Patent Information
- Application Number
- JP2022568318
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-12-10
- Filing Date
- 2021-12-08
- Publication Date
- 2025-02-19
- Estimated Expiration
- 2041-12-08
AI Technical Summary
【0009】 本発明の固体電池は、正極活物質とガーネット型酸化物との焼成時における副反応をより十分に抑制しつつ、ガーネット型酸化物のイオン伝導度の低下をより十分に抑制することができる。
Smart Images

Figure 0007632476000009 
Figure 0007632476000010 
Figure 0007632476000011
Abstract
Description
[Technical field]
[0001] The present invention relates to a solid-state battery. [Background technology]
[0002] In recent years, the demand for batteries as power sources for portable electronic devices such as mobile phones and portable personal computers has expanded significantly. As batteries for such applications, development of sintered solid-state secondary batteries (so-called "solid-state batteries") that use a solid electrolyte as the electrolyte and whose other components are also composed of solids is underway.
[0003] The solid-state battery includes a positive electrode layer, a negative electrode layer, and a solid electrolyte layer laminated between the positive electrode layer and the negative electrode layer. As the positive electrode layer, a positive electrode layer containing a positive electrode active material and a garnet-type oxide is known. For example, Non-Patent Document 1 discloses the presence of a garnet-type oxide in which Sr and Nb are concentrated near the grain boundaries. [Prior art documents] [Non-patent literature]
[0004] [Non-Patent Document 1] S. Ohta et.al., Frontiers in Energy Research (2016) 4, 30(Toyota Central R&D Labs.) Summary of the Invention [Problem to be solved by the invention]
[0005] The inventors of the present invention have found that the following problems occur in solid-state batteries using the above-mentioned conventional positive electrode layer: In particular, there are problems in that a side reaction occurs between the positive electrode active material and the garnet-type oxide during firing, and / or the ionic conductivity of the garnet-type oxide decreases.
[0006] More specifically, when the garnet-type oxide has a chemical composition with a relatively large amount of Li, Li is excessively introduced (or diffused) into the positive electrode active material during firing, and the characteristics of the positive electrode active material are deteriorated. Therefore, by using a garnet-type oxide with a relatively small amount of Li, Li is less likely to be introduced (or diffused) into the positive electrode active material during firing, and the deterioration of the characteristics of the positive electrode active material can be suppressed. However, the decrease in the amount of Li in the garnet-type oxide causes a decrease in ion conductivity, leading to an increase in the resistance of the solid-state battery. This problem is particularly noticeable when a positive electrode active material having a layered rock salt structure is used as the positive electrode active material. If the side reaction during firing of the positive electrode active material and the garnet-type oxide cannot be sufficiently suppressed, for example, the initial utilization rate of the positive electrode active material in a solid-state battery is reduced. Also, if the decrease in the ion conductivity of the garnet-type oxide cannot be sufficiently suppressed, for example, the utilization rate of the positive electrode active material during 1C discharge in a solid-state battery is reduced.
[0007] An object of the present invention is to provide a solid-state battery capable of more sufficiently suppressing a side reaction occurring during firing of a positive electrode active material and a garnet-type oxide while more sufficiently suppressing a decrease in the ionic conductivity of the garnet-type oxide. [Means for solving the problem]
[0008] The present invention relates to a positive electrode layer, a negative electrode layer, and a solid electrolyte layer disposed between the positive electrode layer and the negative electrode layer; A solid-state battery comprising: the positive electrode layer contains a positive electrode active material and an oxide having a garnet-type crystal structure, a Li concentration in the oxide near the interface with the positive electrode active material is lower than a Li concentration in the inside of a particle of the oxide; Regarding. Effect of the Invention
[0009] The solid-state battery of the present invention can more sufficiently suppress side reactions occurring during firing of the positive electrode active material and the garnet-type oxide, while more sufficiently suppressing a decrease in the ionic conductivity of the garnet-type oxide. [Brief description of the drawings]
[0010] [Figure 1] FIG. 2 is a schematic cross-sectional view showing one embodiment of the relationship between a positive electrode active material and a garnet-type oxide in a positive electrode layer of a solid-state battery according to the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view showing another embodiment of the relationship between the positive electrode active material and the garnet-type oxide in the positive electrode layer of the solid battery according to the present invention. [Diagram 3] FIG. 2 is a schematic cross-sectional view showing still another embodiment of the relationship between the positive electrode active material and the garnet-type oxide in the positive electrode layer of the solid state battery according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] [Solid battery] The present invention provides a solid-state battery. In the present specification, the term "solid-state battery" refers in a broad sense to a battery whose components (particularly the electrolyte layer) are made of solids, and in a narrow sense to an "all-solid-state battery" whose components (particularly all components) are made of solids. In the present specification, the term "solid-state battery" includes so-called "secondary batteries" that can be repeatedly charged and discharged, and "primary batteries" that can only be discharged. The "solid-state battery" is preferably a "secondary battery." The term "secondary battery" is not excessively limited by its name, and may also include electrochemical devices such as "electricity storage devices."
[0012] The solid-state battery of the present invention includes a positive electrode layer, a negative electrode layer, and a solid electrolyte layer, and usually has a laminated structure in which a solid electrolyte layer is disposed between the positive electrode layer and the negative electrode layer. The positive electrode layer and the negative electrode layer may each be laminated in two or more layers as long as a solid electrolyte layer is provided between them. The solid electrolyte layer is in contact with the positive electrode layer and the negative electrode layer and is sandwiched between them. The positive electrode layer and the solid electrolyte layer may be integrally sintered together as sintered bodies, and / or the negative electrode layer and the solid electrolyte layer may be integrally sintered together as sintered bodies. The term "integrally sintered together as sintered bodies" means that two or more adjacent or contacting members (particularly layers) are joined by sintering. Here, the two or more members (particularly layers) may be integrally sintered together while being sintered bodies. The solid-state battery of the present invention may be referred to as a "sintered solid-state battery" or a "co-sintered solid-state battery" in the sense that the positive electrode layer and the solid electrolyte layer are sintered together as sintered bodies, and the negative electrode layer and the solid electrolyte layer are sintered together as sintered bodies.
[0013] (Positive electrode layer) In the solid-state battery of the present invention, the positive electrode layer contains a positive electrode active material and an oxide having a garnet-type crystal structure (sometimes referred to as a garnet-type oxide in this specification). The positive electrode layer may have the form of a sintered body containing positive electrode active material particles and garnet-type oxide particles. It is preferable that the positive electrode layer is a layer capable of absorbing and releasing ions (especially lithium ions).
[0014] The positive electrode active material is not particularly limited, and positive electrode active materials known in the field of lithium ion batteries and solid-state batteries can be used. Examples of the positive electrode active material include lithium transition metal composite oxide particles having a layered rock salt structure (hereinafter, sometimes referred to as "layered rock salt type positive electrode active material"), lithium-containing phosphate compound particles having a Nasicon type structure, lithium-containing phosphate compound particles having an olivine type structure, lithium-containing layered oxide particles, and lithium-containing oxide particles having a spinel type structure. The positive electrode active material preferably includes a layered rock salt type positive electrode active material. When the positive electrode active material includes a layered rock salt type positive electrode active material, it has been more difficult to sufficiently suppress both the side reaction during the firing of the positive electrode active material and the garnet type oxide and the decrease in ion conductivity of the garnet type oxide, but even if such a layered rock salt type positive electrode active material is included, both of these can be more sufficiently suppressed.
[0015] The layered rock-salt type positive electrode active material is a lithium transition metal composite oxide. The positive electrode active material has a layered rock-salt type structure, which means that the lithium transition metal composite oxide (particularly its particles) has a layered rock-salt type crystal structure, and in a broad sense, means that the lithium transition metal composite oxide has a crystal structure that can be recognized as a layered rock-salt type crystal structure by a person skilled in the field of batteries. In a narrow sense, the positive electrode active material has a layered rock-salt type structure, which means that the lithium transition metal composite oxide (particularly its particles) is identified as having a layered rock-salt type crystal structure by analyzing the X-ray diffraction pattern by Rietveld analysis or the like. The lithium transition metal composite oxide is a general term for oxides containing lithium and one or more transition metal elements as constituent elements.
[0016] The lithium transition metal composite oxide is, for example, Li x M1 y O 2 , Li x M1 y M2 z O 2In the present invention, M1 is one or more transition metal elements, and preferably contains cobalt, more preferably contains cobalt alone, from the viewpoint of further suppressing side reactions during firing and a decrease in the ionic conductivity of the garnet-type oxide. M2 is aluminum, magnesium, boron, zinc, tin, calcium, strontium, bismuth, sodium, potassium, silicon, phosphorus, etc. The values of x, y, and z are arbitrary.
[0017] Specifically, the lithium transition metal composite oxide is, for example, LiCoO 2 (i.e. lithium cobalt oxide), Li(Co 0.8 Ni 0.1 Mn 0.1 )O 2 , LiNiO 2 , LiVO 2 , LiCrO 2 , LiCo 1 / 3 Ni 1 / 3 Mn 1 / 3 O 2 And so on.
[0018] The layered rock salt type positive electrode active material is preferably lithium cobalt oxide from the viewpoint of further suppressing side reactions during firing and a decrease in the ionic conductivity of the garnet type oxide.
[0019] When the positive electrode layer contains a layered rock salt type positive electrode active material, the content of the layered rock salt type positive electrode active material in the positive electrode layer is usually 20% by volume or more, particularly 20% by volume or more and 100% by volume or less, and from the viewpoint of further suppressing side reactions during firing and a decrease in the ionic conductivity of the garnet-type oxide, is preferably 40% by volume or more and 80% by volume or less, more preferably 45% by volume or more and 70% by volume or less. The positive electrode layer may contain two or more types of layered rock salt type positive electrode active materials, in which case the total content thereof may be within the above range.
[0020] When the positive electrode layer contains a layered rock salt type positive electrode active material, the positive electrode layer may contain a positive electrode active material other than the layered rock salt type positive electrode active material. The content of the positive electrode active material other than the layered rock salt type positive electrode active material is usually 10% by volume or less relative to the entire positive electrode layer, and from the viewpoint of further suppressing side reactions during firing and a decrease in the ion conductivity of the garnet-type oxide, it is preferably 5% by volume or less, and more preferably 0% by volume.
[0021] The positive electrode active material having a Nasicon structure means that the positive electrode active material (particularly its particles) has a Nasicon crystal structure, and in a broad sense, means that the positive electrode active material has a crystal structure that can be recognized as a Nasicon crystal structure by those skilled in the art of solid-state batteries. In a narrow sense, the positive electrode active material having a Nasicon structure in the positive electrode layer means that the positive electrode active material (particularly its particles) shows one or more main peaks corresponding to Miller indices specific to the so-called Nasicon crystal structure at a specified angle of incidence in X-ray diffraction. A positive electrode active material having a Nasicon structure that is preferably used is Li 3 V 2 (PO 4 ) 3 etc.
[0022] The positive electrode active material having an olivine structure means that the positive electrode active material (particularly its particles) has an olivine crystal structure, and in a broad sense, means that the positive electrode active material has a crystal structure that can be recognized as an olivine crystal structure by those skilled in the art of solid-state batteries. In a narrow sense, the positive electrode active material having an olivine structure in the positive electrode layer means that the positive electrode active material (particularly its particles) shows, in X-ray diffraction, one or more main peaks corresponding to Miller indices specific to the so-called olivine crystal structure at a specified angle of incidence. A positive electrode active material having an olivine structure that is preferably used is Li 3 Fe 2 (PO 4 ) 3 , LiMnPO 4 etc.
[0023] The positive electrode active material in the positive electrode layer having a spinel structure means that the positive electrode active material (particularly its particles) has a spinel crystal structure, and in a broad sense, means that the positive electrode active material has a crystal structure that can be recognized as a spinel crystal structure by those skilled in the art of solid-state batteries. In a narrow sense, the positive electrode active material in the positive electrode layer having a spinel structure means that the positive electrode active material (particularly its particles) shows, in X-ray diffraction, one or more main peaks corresponding to Miller indices specific to the so-called spinel crystal structure at a predetermined incident angle. A preferred positive electrode active material having a spinel structure is LiMn 2 O 4 ,LiNi 0.5 Mn 1.5 O 4 , Li 4 Ti 5 O 12 etc.
[0024] The chemical composition of the positive electrode active material may be an average chemical composition. The average chemical composition of the positive electrode active material means the average value of the chemical composition of the positive electrode active material in the thickness direction of the positive electrode layer. The average chemical composition of the positive electrode active material can be analyzed and measured by breaking the solid-state battery and performing composition analysis by EDX (energy dispersive X-ray spectroscopy) in a field of view that includes the entire thickness direction of the positive electrode layer using SEM-EDX.
[0025] The positive electrode active material can be produced, for example, by the following method, or can be obtained as a commercial product. When producing the positive electrode active material, first, a raw material compound containing a predetermined metal atom is weighed so that the chemical composition is a predetermined chemical composition, and water is added and mixed to obtain a slurry. The slurry is then dried, calcined at 700°C to 1000°C for 1 hour to 30 hours, and pulverized to obtain the positive electrode active material.
[0026] The chemical composition and crystal structure of the positive electrode active material in the positive electrode layer may typically change due to elemental diffusion during sintering. The positive electrode active material may have the above-mentioned chemical composition and crystal structure in the solid-state battery after sintering with the negative electrode layer and the solid electrolyte layer.
[0027] The average particle size of the positive electrode active material is not particularly limited and may be, for example, 100 nm to 10 μm, and is preferably 500 nm to 8 μm, more preferably 1 μm to 6 μm, from the viewpoint of further suppressing side reactions during firing and the decrease in ion conductivity of the garnet-type oxide. The average particle size of the positive electrode active material is usually larger than the average particle size of the garnet-type oxide described later.
[0028] The average particle size (arithmetic mean) of the positive electrode active material can be determined, for example, by randomly selecting 10 to 100 particles from an SEM image and simply averaging their particle sizes. The particle diameter is the diameter of a spherical particle when the particle is assumed to be a perfect sphere. Such a particle diameter can be obtained, for example, by cutting out a cross section of a solid-state battery, taking a cross-sectional SEM image using a SEM, calculating the cross-sectional area S of the particle using image analysis software (for example, "A-zo-kun" (manufactured by Asahi Kasei Engineering Co., Ltd.)), and then calculating the particle diameter R using the following formula.
[0029]
number
[0030] The average particle size of the positive electrode active material in the positive electrode layer may be measured by specifying the positive electrode active material based on its composition when measuring the above-mentioned chemical composition.
[0031] The average particle size of the positive electrode active material in the positive electrode layer may usually change due to sintering during the manufacturing process of the solid-state battery. The positive electrode active material may have the above-mentioned average particle size in the solid-state battery after sintering with the negative electrode layer and the solid electrolyte layer.
[0032] A garnet-type oxide is an oxide (particularly a metal oxide) having a garnet-type crystal structure. The term "garnet-type crystal structure" means that the oxide has not only a "garnet-type crystal structure" but also includes a "garnet-like crystal structure". Specifically, the oxide has a crystal structure that can be recognized as a garnet-type or garnet-like crystal structure by a person skilled in the field of solid-state batteries in X-ray diffraction. More specifically, the oxide may show one or more main peaks corresponding to Miller indices specific to the so-called garnet-type crystal structure (diffraction pattern: ICDD Card No. 01-080-6142) at a predetermined incidence angle in X-ray diffraction, or may show one or more main peaks having different incidence angles (i.e., peak positions or diffraction angles) and intensity ratios (i.e., peak intensities or diffraction intensity ratios) from one or more main peaks corresponding to Miller indices specific to the so-called garnet-type crystal structure due to differences in composition as a garnet-like crystal structure. A representative diffraction pattern of a garnet-like crystal structure is, for example, ICDD Card No. 00-045-0109.
[0033] In the present invention, the garnet-type oxide has a predetermined Li concentration gradient between the vicinity of the interface with the positive electrode active material and the inside of the particle. In particular, the Li concentration in the vicinity of the interface with the positive electrode active material in the garnet-type oxide is lower than the Li concentration in the inside of the particle of the garnet-type oxide. By making the Li concentration in the vicinity of the interface with the positive electrode active material in the garnet-type oxide lower than the Li concentration in the inside of the particle, it is possible to minimize the decrease in the ionic conductivity of the garnet-type oxide while suppressing side reactions with the positive electrode active material (i.e., introduction or diffusion of Li into the positive electrode active material). As a result, it is possible to manufacture a low-resistance solid-state battery that is sufficiently excellent due to the ionic conductivity of the garnet-type oxide while improving the utilization rate of the positive electrode active material in the solid-state battery.
[0034] In the positive electrode layer, the positive electrode active material and the garnet-type oxide (particularly at least a part thereof) may be disposed in direct contact with each other, or may be disposed in indirect contact with each other via an interface phase. For example, as shown in Fig. 1, the positive electrode active material particles 1 may be arranged in contact with each other with a smaller contact area while having a gap between adjacent garnet-type oxide particles 2. In this case, the garnet-type oxide particles may also be arranged in contact with each other with a smaller contact area while having a gap between them, as shown in Fig. 1. Fig. 1 shows a schematic cross-sectional view showing one embodiment of the relationship between the positive electrode active material and the garnet-type oxide in the positive electrode layer of the solid battery according to the present invention. Furthermore, as shown in Fig. 2, for example, as a result of the progress of heat treatment (e.g., sintering), the positive electrode active material particles 1 may be arranged in contact with each other over a larger contact area while having fewer voids between adjacent garnet-type oxide particles 2. In this case, the garnet-type oxide particles may also be arranged in contact with each other over a larger contact area while having fewer voids between them, as shown in Fig. 2. Fig. 2 shows a schematic cross-sectional view illustrating another embodiment of the relationship between the positive electrode active material and the garnet-type oxide in the positive electrode layer of the solid-state battery according to the present invention. Furthermore, as shown in Fig. 3, for example, the heat treatment (e.g., sintering) may progress further so that the positive electrode active material particles 1 are in contact with adjacent garnet-type oxides (or particles thereof) 2 with no voids and with a larger contact area. In this case, the garnet-type oxide particles may also be in contact with each other with no voids and with a larger contact area as shown in Fig. 3. Fig. 3 is a schematic cross-sectional view showing another embodiment of the relationship between the positive electrode active material and the garnet-type oxide in the positive electrode layer of the solid-state battery according to the present invention. Furthermore, for example, the positive electrode active material particles 1 may be arranged in contact with adjacent garnet-type oxides (or particles thereof) 2, with the adjacent garnet-type oxides (or particles thereof) 2 having a combination of the forms shown in FIGS.
[0035] In a cross-sectional view of the solid-state battery of the present invention (particularly a cross-sectional view by a TEM or STEM photograph), the garnet-type oxide particle is usually divided into a peripheral region 21 and an internal region 22 as shown in FIG. 1, and as heat treatment (e.g., sintering) progresses, the peripheral region 21 may be connected and shared among a plurality of garnet-type oxide particles as shown in FIG. 2 to FIG. 3. The peripheral region 21 and the internal region 22 can usually be distinguished by a difference in contrast (i.e., brightness or shading) caused by a difference in chemical composition, for example, in a cross-sectional view by a scanning transmission electron microscope (STEM)-dark field (DF) image. In this specification, the cross-sectional view or cross-sectional view may be a cross-sectional view or cross-sectional view when a solid-state battery (particularly its positive electrode layer) is cut in any direction, and may be, for example, a cross-sectional view or cross-sectional view when the positive electrode layer is cut in a direction perpendicular to its main surface.
[0036] The interface vicinity of the garnet-type oxide particle is specifically a region in the garnet-type oxide 2 that is within 50 nm from the interface R with the positive electrode active material 1 in the cross-sectional view (i.e., the distance from the interface R toward the garnet-type oxide 2) and corresponds to the shaded region represented by the symbol "23" in Figs. 1 to 3, for example. The interface vicinity 23 is usually disposed in the peripheral region 21 of the garnet-type oxide. The particle interior 22 is an inner region surrounded by the peripheral region 21 in the cross-sectional view. In the solid-state battery of the present invention, the Li concentration of the interface vicinity 23 with the positive electrode active material 1 in the garnet-type oxide 2 in the positive electrode layer is lower than the Li concentration of the particle interior 22 of the garnet-type oxide. When the positive electrode active material and the garnet-type oxide are indirectly in contact with each other via an interface phase, the interface R is the interface between the interface phase and the garnet-type oxide.
[0037] In the present invention, attention is focused on five arbitrary positive electrode active material particles 1 in each of the cut cross sections (TEM cross section) in two arbitrary directions of the positive electrode layer (a total of 10 positive electrode active material particles). Next, for each positive electrode active material particle 1, the Li concentration is obtained at 10 arbitrary points in the interface vicinity 23 of the adjacent garnet-type oxide 2, and the average Li concentration in the interface vicinity 23 for the total of 10 positive electrode active material particles is obtained. Furthermore, for each positive electrode active material particle 1, the Li concentration is obtained at 10 arbitrary points in the particle interior 22 of the adjacent garnet-type oxide 2, and the average Li concentration in the particle interior 22 for the total of 10 positive electrode active material particles is obtained. As a result, the average Li concentration in the interface vicinity 23 is lower than the average Li concentration in the particle interior 22.
[0038] In this specification, the Li concentration in the interface vicinity 23 and particle interior 22 may be directly measured using TEM-EELS (electron energy loss spectroscopy). Alternatively, the molar ratio of elements other than Li may be analyzed using TEM-EDX (energy dispersive X-ray spectroscopy), and then the Li amount may be calculated from the following formula (I). The average Li concentration can be obtained by point analyzing a predetermined number of points in each region and averaging the results.
[0039] The Li concentration gradient of the garnet-type oxide in the positive electrode layer in the solid-state battery of the present invention will be described in detail below by taking as an example a preferred embodiment in which the garnet-type oxide has a specific chemical composition.
[0040] From the viewpoint of further suppressing side reactions during firing and a decrease in the ionic conductivity of the garnet-type oxide, the garnet-type oxide preferably has a chemical composition represented by the following general formula (I). More specifically, from the viewpoint of further suppressing side reactions during firing and a decrease in the ionic conductivity of the garnet-type oxide, the interface vicinity 23 and the particle interior 22 of the garnet-type oxide preferably each independently have a chemical composition represented by the following general formula (I). More specifically, each of the garnet-type oxide particles includes a peripheral region and its internal region as described above, and the interface vicinity with the positive electrode active material arranged in the peripheral region and the particle interior surrounded by the peripheral region preferably each independently have a chemical composition represented by the following general formula (I).
[0041] [ka]
[0042] In formula (I), A is one or more elements capable of forming a solid solution in the Li site of the garnet-type oxide, specifically, A is one or more elements selected from the group consisting of Mg (magnesium), Al (aluminum), Ga (gallium), Sc (scandium) and Fe (iron) (hereinafter sometimes referred to as "group a"). B I is one or more elements selected from the group consisting of elements that can take a trivalent valence among elements belonging to Groups 1 to 3 that can take an 8-coordination with oxygen. I Specifically, is one or more elements selected from the group consisting of La (lanthanum), Y (yttrium), Pr (praseodymium), Nd (neodymium), Pm (promethium), Sm (samarium), Eu (europium), Gd (gadolinium), Tb (terbium), Dy (dysprosium), Ho (holminium), Er (erbium), Tm (thulium), Yb (ytterbium) and Lu (lutetium) (hereinafter sometimes referred to as "group bI"). IPreferably, B contains La (lanthanum) from the viewpoint of further suppressing side reactions during firing and the decrease in the ionic conductivity of the garnet-type oxide. I may contain La (lanthanum) alone. B II is one or more elements selected from the group consisting of elements belonging to Groups 1 to 3 that can form eight-coordinated bonds with oxygen and can have a valence other than trivalent. II For details, see the bivalent B II Ca (calcium), Sr (strontium) and Ba (barium) as well as tetravalent B II and Ce (cerium) as an element (hereinafter sometimes referred to as "Group bII"). D I D is one or more elements selected from the group consisting of transition elements capable of forming 6-coordination with oxygen and elements capable of forming a tetravalent valence among typical elements belonging to groups 12 to 15. I Specifically, D is one or more elements selected from the group consisting of Zr (zirconium), Ti (titanium), Hf (hafnium), Ge (germanium) and Sn (tin) (hereinafter sometimes referred to as "group dI"). I Preferably, D contains Zr (zirconium) from the viewpoint of further suppressing side reactions during firing and the decrease in the ionic conductivity of the garnet-type oxide. I may contain Zr (zirconium) alone. D II D is one or more elements selected from the group consisting of transition elements capable of forming 6-coordination with oxygen and elements capable of forming valences other than 4 among the typical elements belonging to groups 12 to 15. II For details, see Trivalent D II Sc (Scandium) as 5-valent D II Ta (tantalum), Nb (niobium), Sb (antimony) and Bi (bismuth) as well as hexavalent D IID is one or more elements selected from the group consisting of Mo (molybdenum), W (tungsten) and Te (tellurium) (hereinafter sometimes referred to as "Group dII"). II From the viewpoint of further suppressing side reactions during firing and the decrease in the ionic conductivity of the garnet-type oxide, is preferably one or more elements selected from the group consisting of Bi (bismuth) and Ta (tantalum), and more preferably contains Bi (bismuth). II When the material contains Bi, the sinterability at the interface with the positive electrode active material is improved, making it easier to increase the contact area with the positive electrode active material, and further improving the utilization rate.
[0043] A, B I , B II , D I and D. II is as described above in the vicinity of the interface 23 and in the particle interior 22, and may be within the above ranges independently. I , B II , D I , D II From the viewpoint of further suppressing side reactions during firing and a decrease in the ionic conductivity of the garnet-type oxide, the following embodiment 1 is preferable.
[0044] (Embodiment 1) Near-interface area 23: A is one or more elements selected from group a; B I is one or more elements selected from group bI, and from the viewpoint of further suppressing side reactions during firing and a decrease in the ionic conductivity of the garnet-type oxide, preferably contains La (lanthanum), and in particular may contain only La (lanthanum); B II is one or more elements selected from group bII; D Iis one or more elements selected from group dI, and from the viewpoint of further suppressing side reactions during firing and a decrease in the ionic conductivity of the garnet-type oxide, preferably contains Zr (zirconium), and in particular may contain only Zr (zirconium); D II is one or more elements selected from Group dII, and from the viewpoint of further suppressing side reactions during firing and a decrease in the ionic conductivity of the garnet-type oxide, is preferably one or more elements selected from the group consisting of Bi (bismuth) and Ta (tantalum), more preferably contains Bi (bismuth), and in particular may contain only Bi (bismuth);
[0045] Particle inside 21: A is one or more elements selected from group a, and in particular may be the same element as A in the vicinity of the interface in this embodiment; B I is one or more elements selected from group bI, and preferably contains La (lanthanum), particularly may contain only La (lanthanum), from the viewpoint of further suppressing side reactions during firing and a decrease in the ionic conductivity of the garnet-type oxide; B I In particular, in this embodiment, B in the vicinity of the interface I may be an element similar to; B II is one or more elements selected from group bII, and in particular, B in the vicinity of the interface in this embodiment II may be an element similar to; D I is one or more elements selected from group dI, and preferably contains Zr (zirconium), particularly may contain only Zr (zirconium), from the viewpoint of further suppressing side reactions during firing and a decrease in the ionic conductivity of the garnet-type oxide; D I is particularly the D near the interface in this embodiment. I may be an element similar to; D IIis one or more elements selected from Group dII, and from the viewpoint of further suppressing side reactions during firing and a decrease in the ionic conductivity of the garnet-type oxide, preferably contains one or more elements selected from the group consisting of Bi (bismuth) and Ta (tantalum) (hereinafter sometimes referred to as "Group dII'"), more preferably contains one or more elements selected from the above Group dII', and further preferably contains Bi (bismuth), and in particular may contain only Bi (bismuth) and Ta (tantalum).
[0046] In formula (I), p is calculated by formula (i): p=ax-(3-b)y+(d-4)z (i) It is expressed as:
[0047] In formula (i), a is the average valence of A. The average valence of A is a value represented by the formula: (n1×r+n2×s+n3×t) / (n1+n2+n3) when, for example, A contains n1 element X with a valence of r+, n2 element Y with a valence of s+, and n3 element Z with a valence of t+. b is B II is the average valence of B II The average valence of B II For example, when n1 element X with valence r+, n2 element Y with valence s+, and n3 element Z with valence t+ are found, the average valence of A is expressed by the same formula as above. d is D II is the average valence of;D II The average valence of D II For example, when n1 element X with valence r+, n2 element Y with valence s+, and n3 element Z with valence t+ are found, the average valence of A is expressed by the same formula as above.
[0048] In the present invention, when p is expressed by the above-mentioned formula (i), p (hereinafter referred to as "p1") in the interface vicinity 23 of the garnet-type oxide is larger than p (hereinafter referred to as "p2") in the particle interior 22. In detail, both the interface vicinity 23 and the particle interior 22 of the garnet-type oxide are expressed by the above-mentioned general formula (I), and when the interface vicinity 23 and the particle interior 22 are each expressed by the general formula (I), p1 in the interface vicinity is larger than p2 in the particle interior. Such a relationship between p1 in the interface vicinity 23 and p2 in the particle interior 22 has the same meaning as the relationship regarding the concentration gradient of the Li concentration in the interface vicinity 23 and the Li concentration in the particle interior 22 described above. Note that p is usually smaller than α in each of the interface vicinity and the particle interior.
[0049] The following will explain α, β, γ, ω, x, y, and z in formula (I) separately for the interface vicinity 23 and the particle interior 22.
[0050] The interface vicinity portion 23 usually satisfies the following condition K in formula (I), and the particle interior 22 usually satisfies the following condition N in formula (I).
[0051] (Near the interface: Condition K) α satisfies 5.0≦α≦8.0, and from the viewpoint of further suppressing side reactions during firing and a decrease in the ionic conductivity of the garnet-type oxide, preferably satisfies 5.5≦α≦7.5, more preferably 5.5≦α≦7.0, even more preferably 6.0≦α≦6.8, particularly preferably 6.2≦α≦6.8, and most preferably 6.2≦α≦6.6. β satisfies 2.5≦β≦3.5, and from the viewpoint of further suppressing side reactions during firing and a decrease in the ionic conductivity of the garnet-type oxide, preferably satisfies 2.6≦β≦3.4, more preferably 2.7≦β≦3.3, even more preferably 2.8≦β≦3.2, particularly preferably 2.9≦β≦3.1, and is most preferably 3.0. γ satisfies 1.5≦γ≦2.5, and from the viewpoint of further suppressing side reactions during firing and a decrease in the ionic conductivity of the garnet-type oxide, preferably satisfies 1.6≦γ≦2.4, more preferably 1.7≦γ≦2.3, even more preferably 1.8≦γ≦2.2, particularly preferably 1.9≦γ≦2.1, and is most preferably 2.0. ω satisfies 11≦ω≦13, and from the viewpoint of further suppressing side reactions during firing and the decrease in ionic conductivity of the garnet-type oxide, preferably satisfies 11≦ω≦12.5, more preferably 11.5≦ω≦12.5, and even more preferably "12-δ". δ indicates the amount of oxygen vacancy and may be 0. δ usually satisfies 0≦δ<1. The amount of oxygen vacancy δ cannot be quantitatively analyzed even with the latest equipment, so it may be considered to be 0. x satisfies 0≦x≦1.0, and from the viewpoint of further suppressing side reactions during firing and a decrease in the ionic conductivity of the garnet-type oxide, preferably satisfies 0≦x≦0.8, more preferably 0≦x≦0.6, even more preferably 0≦x≦0.4, particularly preferably 0≦x≦0.2, and most preferably 0. y is a value smaller than β and usually satisfies 0≦y≦1.0. From the viewpoint of further suppressing side reactions during firing and a decrease in the ionic conductivity of the garnet-type oxide, y preferably satisfies 0≦y≦0.8, more preferably 0≦y≦0.6, even more preferably 0≦y≦0.4, particularly preferably 0≦y≦0.2, and most preferably 0. z is a value equal to or less than γ, and usually satisfies 0.4≦z≦2.2. From the viewpoint of further suppressing side reactions during firing and a decrease in the ionic conductivity of the garnet-type oxide, it preferably satisfies 0.5≦y≦2.1, more preferably 0.7≦z≦2.1, even more preferably 0.9≦z≦2.1, particularly preferably 1.5≦z≦2.1, and most preferably 1.8≦z≦2.0. 1 is usually defined as z inside the particle (hereafter z 2 z 1 and z 2 is usually 0.1≦z1 -z 2 ≦2.0, and from the viewpoint of further suppressing side reactions during firing and a decrease in the ionic conductivity of the garnet-type oxide, 0.3≦z 1 -z 2 ≦1.5, more preferably 1.0≦z 1 -z 2 ≦1.5.
[0052] (Inside particle: Condition N) α satisfies 5.0≦α≦8.0, and from the viewpoint of further suppressing side reactions during firing and a decrease in the ionic conductivity of the garnet-type oxide, preferably satisfies 5.5≦α≦7.5, more preferably 5.5≦α≦7.0, even more preferably 6.0≦α≦6.8, particularly preferably 6.2≦α≦6.8, and most preferably 6.2≦α≦6.6. β satisfies 2.5≦β≦3.5, and from the viewpoint of further suppressing side reactions during firing and a decrease in the ionic conductivity of the garnet-type oxide, preferably satisfies 2.6≦β≦3.4, more preferably 2.7≦β≦3.3, even more preferably 2.8≦β≦3.2, particularly preferably 2.9≦β≦3.1, and is most preferably 3.0. γ satisfies 1.5≦γ≦2.5, and from the viewpoint of further suppressing side reactions during firing and a decrease in the ionic conductivity of the garnet-type oxide, preferably satisfies 1.6≦γ≦2.4, more preferably 1.7≦γ≦2.3, even more preferably 1.8≦γ≦2.2, particularly preferably 1.9≦γ≦2.1, and is most preferably 2.0. ω satisfies 11≦ω≦13, and from the viewpoint of further suppressing side reactions during firing and the decrease in ionic conductivity of the garnet-type oxide, preferably satisfies 11≦ω≦12.5, more preferably 11.5≦ω≦12.5, and even more preferably "12-δ". δ indicates the amount of oxygen vacancy and may be 0. δ usually satisfies 0≦δ<1. The amount of oxygen vacancy δ cannot be quantitatively analyzed even with the latest equipment, so it may be considered to be 0. x satisfies 0≦x≦1.0, and from the viewpoint of further suppressing side reactions during firing and a decrease in the ionic conductivity of the garnet-type oxide, preferably satisfies 0≦x≦0.8, more preferably 0≦x≦0.6, even more preferably 0≦x≦0.4, particularly preferably 0≦x≦0.2, and most preferably 0. y is a value smaller than β and usually satisfies 0≦y≦1.0. From the viewpoint of further suppressing side reactions during firing and a decrease in the ionic conductivity of the garnet-type oxide, y preferably satisfies 0≦y≦0.8, more preferably 0≦y≦0.6, even more preferably 0≦y≦0.4, particularly preferably 0≦y≦0.2, and most preferably 0. z is a value equal to or less than γ and usually satisfies 0.1≦z≦1.0. From the viewpoint of further suppressing side reactions during firing and a decrease in the ionic conductivity of the garnet-type oxide, z preferably satisfies 0.2≦y≦0.9, more preferably 0.3≦z≦0.9, even more preferably 0.4≦z≦0.8, particularly preferably 0.5≦z≦0.7, and most preferably 0.55≦z≦0.65.
[0053] In the present invention, as described above, the interface vicinity portion 23 and the particle interior 22 of the garnet-type oxide are both represented by the above general formula (I), and when the interface vicinity portion 23 and the particle interior 22 are each represented by general formula (I) and p is represented by the above calculation formula (i), p of the interface vicinity portion 23 (i.e., p1) is larger than p of the particle interior 22 (i.e., p2).
[0054] The p1 of the interface vicinity 23 and the p2 of the particle interior 22 can be values obtained by the following method. Focus on any five positive electrode active material particles 1 in each of the cut cross sections (TEM cross section) in any two directions of the positive electrode layer (a total of 10 positive electrode active material particles). Next, for each positive electrode active material particle 1, the chemical composition is obtained at any 10 points in the interface vicinity 23 of the adjacent garnet-type oxide 2, and the average p1 value of the interface vicinity 23 for the total of 10 positive electrode active material particles is obtained. Furthermore, for each positive electrode active material particle 1, the chemical composition is obtained at any 10 points in the particle interior 22 of the adjacent garnet-type oxide 2, and the average p2 value of the particle interior 22 for the total of 10 positive electrode active material particles is obtained. As a result, it is sufficient that the average p1 value of the interface vicinity 23 is larger than the average p2 value of the particle interior 22.
[0055] The chemical compositions of the interface vicinity 23 and particle interior 22 in the garnet-type oxide of the present invention may be measured by quantitative analysis (composition analysis) using TEM-EDX (energy dispersive X-ray spectroscopy). The method for measuring the chemical compositions of the interface vicinity 23 and particle interior 22 is not particularly limited, but may be, for example, TEM-EELS (transmission electron microscope-electron energy loss spectroscopy) measurement.
[0056] From the viewpoint of further suppressing side reactions during sintering and a decrease in the ionic conductivity of the garnet-type oxide, p1 of the interface vicinity portion 23 and p2 of the particle interior 22 preferably satisfy the following relational expression of embodiment e1, more preferably the following relational expression of embodiment e2, even more preferably the following relational expression of embodiment e3, particularly preferably the following relational expression of embodiment e4, sufficiently preferably the following relational expression of embodiment e5, even more sufficiently preferably the following relational expression of embodiment e6, even more sufficiently preferably the following relational expression of embodiment e7, and most preferably the following relational expression of embodiment e8:
[0057] Embodiment e1: 0.1≦p1-p2. Embodiment e2: 0.1≦p1-p2≦2.0. Embodiment e3: 0.25≦p1-p2≦1.8. Embodiment e4: 0.25≦p1-p2≦1.5. Embodiment e5: 0.5≦p1-p2≦1.5. Embodiment e6: 0.65≦p1-p2≦1.5. Embodiment e7: 0.7≦p1-p2≦1.5. Embodiment e8: 1.0≦p1-p2≦1.5.
[0058] From the viewpoint of further suppressing side reactions during firing and a decrease in the ionic conductivity of the garnet-type oxide, p1 of the interface vicinity portion 23 preferably satisfies the relational formula of the following embodiment f1, more preferably the relational formula of the following embodiment f2, even more preferably the relational formula of the following embodiment f3, particularly preferably the relational formula of the following embodiment f4, sufficiently preferably the relational formula of the following embodiment f5, even more sufficiently preferably the relational formula of the following embodiment f6, and most preferably the relational formula of the following embodiment f7: Embodiment f1: 0.4 <p1≦2.0。 Embodiment f2: 0.5≦p1≦2.0. Embodiment f3: 0.7≦p1≦2.0. Embodiment f4: 1.2≦p1≦2.0. Embodiment f5: 1.5≦p1≦2.0. Embodiment f6: 1.7≦p1≦2.0. Embodiment f7: 1.8≦p1≦2.0.
[0059] From the viewpoint of further suppressing side reactions during firing and a decrease in the ionic conductivity of the garnet-type oxide, p2 in the particle interior 22 preferably satisfies the following relational formula of embodiment g1, more preferably the following relational formula of embodiment g2, even more preferably the following relational formula of embodiment g3, particularly preferably the following relational formula of embodiment g4, sufficiently preferably the following relational formula of embodiment g5, even more sufficiently preferably the following relational formula of embodiment g6, and most preferably the following relational formula of embodiment g7: Embodiment g1: 0.1≦p2≦1.5. Embodiment g2: 0.1≦p2≦1.2. Embodiment g3: 0.1≦p2≦1.0. Embodiment g4: 0.3≦p2≦1.0. Embodiment g5: 0.3≦p2≦0.7. Embodiment g6: 0.5≦p2≦0.7. Embodiment g7: 0.55≦p2≦0.7.
[0060] From the viewpoint of further suppressing side reactions during firing and a decrease in the ionic conductivity of the garnet-type oxide, the garnet-type oxide preferably has a chemical composition represented by the following general formula (II): In particular, from the viewpoint of further suppressing side reactions during firing and a decrease in the ionic conductivity of the garnet-type oxide, the interface vicinity portion 23 and the particle interior 22 of the garnet-type oxide preferably each independently have a chemical composition represented by the following general formula (II):
[0061] [ka]
[0062] In formula (II), D II is D in general formula (I) II For example, D II is D in general formula (I)II is the same as: In formula (II), z in the vicinity of the interface is the same as z in condition K in formula (I), and in the interior of the particle, z is the same as z in condition N in formula (I). In formula (II), ω is the same as ω under condition K in formula (I) in the vicinity of the interface, and is the same as ω under condition N in formula (I) in the interior of the particle. In formula (II), p is expressed as p=(d-4)z.
[0063] General formula (II) is one embodiment included in the above general formula (I). Therefore, when the garnet-type oxide (particularly the interface vicinity portion 23 and the particle interior 22) has a chemical composition represented by general formula (II), p1 and p2 calculated from general formula (II) should satisfy the relational expression of p1 and p2 in the above general formula (I).
[0064] The average particle size of the garnet-type oxide is not particularly limited and may be, for example, 10 nm to 5 μm, and is preferably 50 nm to 1 μm, more preferably 100 nm to 800 nm, from the viewpoint of further suppressing side reactions during firing and a decrease in the ionic conductivity of the garnet-type oxide. The average particle size of the garnet-type oxide can be measured by the same method as that of the average particle size of the positive electrode active material described above.
[0065] The content of the garnet-type oxide is usually 10% by volume or more, particularly 20% by volume or more and 80% by volume or less, based on the entire positive electrode layer, and from the viewpoint of further suppressing side reactions during firing and a decrease in the ionic conductivity of the garnet-type oxide, it is preferably 30% by volume or more and 80% by volume or less, more preferably 30% by volume or more and 70% by volume or less. The positive electrode layer may contain two or more kinds of garnet-type oxides, and in that case, the total content thereof may be within the above range.
[0066] As described above, the garnet-type oxide has a Li concentration gradient (e.g., the p-value gradient in the above general formulas (I) and (II)) between the interface vicinity 23 and the particle interior 22, and therefore can also be called a "Li concentration gradient structure type garnet oxide."
[0067] In the positive electrode layer, the Li concentration gradient (e.g., the p value gradient in the above general formulas (I) and (II)) that the garnet-type oxide has between the interface vicinity portion 23 and the particle interior 22 can be formed by using a pre-produced core-shell structure garnet-type oxide when producing the positive electrode layer.
[0068] The core-shell garnet oxide has a core made of a garnet oxide having a relatively high Li concentration, and a shell layer made of a garnet oxide having a relatively low Li concentration. Specifically, such a core-shell garnet oxide can be produced by making the core made of a garnet oxide having a relatively small p, and making the shell made of a garnet oxide having a relatively large p. More specifically, the core-shell garnet oxide can be obtained by heat-treating (for example, at least calcining) a garnet oxide layer having a relatively large p as a shell layer around a garnet oxide particle having a relatively small p as a core particle. More specifically, the core particle is mixed with a solution in which a material for forming the shell layer is dissolved, the solvent is evaporated, and then heat-treated to obtain a garnet oxide particle having a shell layer covering the core particle. Furthermore, the garnet oxide having the shell layer covering the garnet oxide particle can be heat-treated to obtain a core-shell garnet oxide. However, the above manufacturing method is only one example for obtaining a garnet-type oxide having a Li concentration gradient, and the oxide may be produced by other manufacturing methods.
[0069] The core particle is a garnet-type oxide particle with a relatively small p, and examples thereof include materials similar to the garnet-type oxides having the internal chemical composition of the particle represented by the above general formula (I) or general formula (II).
[0070] The core particles can be produced by the following method. A raw material compound containing a predetermined metal atom is weighed out so as to have a predetermined chemical composition, and water is added and mixed to obtain a slurry. The slurry is then dried, calcined at 700°C to 1000°C for 1 hour to 30 hours, and pulverized to obtain the core particles.
[0071] The average particle size of the core particles is not particularly limited as long as the average particle size of the garnet-type oxide is within the above range, and may be, for example, 5 nm or more and 4 μm or less, and is preferably 40 nm or more and 0.8 μm or less, more preferably 80 nm or more and 700 nm or less, from the viewpoint of further suppressing side reactions during firing and a decrease in the ion conductivity of the garnet-type oxide. The average particle size of the core particles can be measured by the same method as that of the average particle size of the positive electrode active material described above.
[0072] The material for forming the shell layer is a material for forming a garnet-type oxide layer having a relatively large p as the shell layer, for example, a material mixture for forming a layer composed of a garnet-type oxide having a relatively large p. The mixing ratio in the material mixture may be such that the shell layer has a predetermined chemical composition after sintering. As the garnet-type oxide having a relatively large p as the shell layer, for example, a material similar to the garnet-type oxide having the chemical composition in the vicinity of the interface represented by the above general formula (I) or general formula (II) can be mentioned.
[0073] The average thickness of the shell layer is not particularly limited as long as the average particle size of the garnet-type oxide is within the above range, and may be, for example, 5 nm or more and 10 μm or less. From the viewpoint of further suppressing side reactions during firing and a decrease in the ionic conductivity of the garnet-type oxide, the average thickness is preferably 10 nm or more and 2 μm or less, and more preferably 20 nm or more and 1 μm or less.
[0074] In this specification, the average thickness of the shell layer can be calculated by subjecting a core particle having a shell layer to TEM measurement, measuring the thickness of the shell layer at any 20 points, and averaging the measurements.
[0075] The content of the material for forming the shell layer in the slurry is not particularly limited as long as a core-shell structured garnet-type oxide is obtained, and may be, for example, 1 mol % or more and 70 mol % or less, particularly 10 mol % or more and 50 mol % or less, relative to 100 mol % of the core particles.
[0076] The solvent is not particularly limited as long as it can dissolve the material for forming the shell layer, and for example, a solvent that can be used in the production of a positive electrode layer, a negative electrode layer, or a solid electrolyte layer in the field of solid-state batteries is used. The solvent is usually a solvent that can be used with the binder described below. Examples of such solvents include alcohols such as 2-methoxyethanol.
[0077] The heat treatment conditions for forming the shell layer are not particularly limited as long as a core-shell structure garnet-type oxide can be obtained. The heat treatment temperature may be, for example, 600°C or more and 1100°C or less, particularly 700°C or more and 950°C or less. The heat treatment time may be, for example, 10 minutes or more and 1440 minutes or less, particularly 60 minutes or more and 600 minutes or less.
[0078] The positive electrode layer may contain a metal oxide (e.g., a so-called solid electrolyte) (hereinafter referred to as other metal oxide) other than a garnet-type oxide. In this case, the content of the other metal oxide is usually 10% by volume or less with respect to the entire positive electrode layer, and from the viewpoint of further suppressing side reactions during firing and a decrease in the ionic conductivity of the garnet-type oxide, the content is preferably 5% by volume or less, and more preferably 0% by volume.
[0079] The positive electrode layer may further contain a sintering aid and / or a conductive aid.
[0080] The sintering aid may be any sintering aid known in the field of solid-state batteries. The composition of such a sintering aid preferably contains at least Li (lithium), B (boron), and O (oxygen), and the molar ratio of Li to B (Li / B) is preferably 2.0 or more. Specific examples of such sintering aids include, for example, Li 4 B 2 O5 , Li 3 BO 3 , (Li 2.7 Al 0.3 )BO 3 , Li 2.8 (B 0.8 C 0.2 )O 3 , LiBO 2 Examples include:
[0081] The content of the sintering aid is not particularly limited, and is, for example, preferably from 0.1 vol % to 20 vol %, and more preferably from 1 vol % to 10 vol %, based on the entire positive electrode layer.
[0082] The conductive assistant may be any conductive assistant known in the field of solid-state batteries. Examples of conductive assistants that are preferably used include metal materials such as Ag (silver), Au (gold), Pd (palladium), Pt (platinum), Cu (copper), Sn (tin), and Ni (nickel); and carbon materials such as acetylene black, Ketjen black, Super P (registered trademark), and carbon nanotubes such as VGCF (registered trademark). The shape of the carbon material is not particularly limited, and any shape such as spherical, plate, or fibrous may be used.
[0083] The content of the conductive assistant is not particularly limited, and is preferably, for example, 50 volume % or less (particularly, 0 volume % or more and 50 volume % or less) and more preferably 40 volume % or less (particularly, 0 volume % or more and 40 volume % or less) relative to the entire positive electrode layer.
[0084] The thickness of the positive electrode layer is usually 0.1 to 30 μm, for example, preferably 1 to 20 μm. The thickness of the positive electrode layer is the average value of thicknesses measured at any 10 points in an SEM image.
[0085] In the positive electrode layer, the porosity is not particularly limited, and is preferably 20 vol % or less, more preferably 15 vol % or less, and further preferably 10 vol % or less.
[0086] The porosity of the positive electrode layer was measured from an SEM image after FIB cross-section processing.
[0087] The positive electrode layer is a layer that may be called a “positive electrode active material layer.” The positive electrode layer may have a so-called positive electrode current collector or positive electrode current collector layer.
[0088] (Negative electrode layer) In the solid-state battery of the present invention, the negative electrode layer is not particularly limited. The negative electrode layer usually contains a negative electrode active material. The negative electrode layer is preferably a layer capable of absorbing and releasing ions (particularly lithium ions).
[0089] The negative electrode active material is not particularly limited, and any negative electrode active material known in the field of solid-state batteries can be used. Examples of the negative electrode active material include carbon materials such as graphite, graphite-lithium compounds, lithium metal, lithium alloy particles, phosphoric acid compounds having a Nasicon structure, Li-containing oxides having a spinel structure, β II -Li 3 VO 4 Type structure, γ II -Li 3 VO 4 The negative electrode active material includes an oxide having a lithium ion-type structure. II -Li 3 VO 4 Type structure, γ II -Li 3 VO 4 It is preferable to use a Li-containing oxide having a type structure.
[0090] In the negative electrode layer, the oxide is β II -Li 3 VO 4 The term "having a β-type structure" means that the oxide (particularly the particles) is a β-type structure. II -Li 3 VO 4 This means that the solid-state battery has a crystal structure of the β type. II -Li 3 VO 4 In the narrow sense, the oxide in the negative electrode layer has a crystal structure that can be recognized as a β-type crystal structure. II -Li3 VO 4 The term "having a β-type structure" means that the oxide (particularly the particles) has a β-type structure in X-ray diffraction. II -Li 3 VO 4 This means that the crystal structure of the type exhibits one or more major peaks corresponding to Miller indices specific to the type at a given angle of incidence. II -Li 3 VO 4 Li-containing oxides having the Li-type structure include Li 3 VO 4 Examples include:
[0091] In the negative electrode layer, the oxide is γ II -Li 3 VO 4 The term "having a γ-type structure" means that the oxide (particularly the particles) is a γ-type structure. II -Li 3 VO 4 This means that the solid-state battery has a crystal structure of the γ type. In a broad sense, this is referred to as γ II -Li 3 VO 4 In the narrow sense, the oxide in the negative electrode layer has a crystal structure that can be recognized as a γ-type crystal structure. II -Li 3 VO 4 The term "having a γ-type structure" means that the oxide (particularly the particles) has a γ-type structure in X-ray diffraction. II -Li 3 VO 4 This means that the crystal structure of the type exhibits one or more major peaks corresponding to Miller indices specific to the type at a given angle of incidence (x-axis). II -Li 3 VO 4 Li-containing oxides having the Li-type structure include Li 3.2 V 0.8 S 0.2 O 4 Examples include:
[0092] The chemical composition of the negative electrode active material may be an average chemical composition. The average chemical composition of the negative electrode active material means the average value of the chemical composition of the negative electrode active material in the thickness direction of the negative electrode layer. The average chemical composition of the negative electrode active material can be analyzed and measured by breaking the solid-state battery and performing composition analysis by EDX (energy dispersive X-ray spectroscopy) in a field of view that includes the entire thickness direction of the negative electrode layer using SEM-EDX.
[0093] The negative electrode active material can be produced, for example, by the same method as that for the positive electrode active material, or can be obtained as a commercially available product.
[0094] The chemical composition and crystal structure of the anode active material in the anode layer may usually be changed by elemental diffusion during sintering in the manufacturing process of the solid-state battery. The anode active material may have the average chemical composition and crystal structure described above in the solid-state battery after sintering with the cathode layer and the solid electrolyte layer.
[0095] The content of the negative electrode active material in the negative electrode layer is not particularly limited, and is, for example, preferably 50% or more (particularly 50% to 99%), more preferably 70% to 95%, and even more preferably 80% to 90% of the entire negative electrode layer.
[0096] The negative electrode layer may further contain a so-called solid electrolyte, a sintering aid, and / or a conductive aid.
[0097] The solid electrolyte that may be contained in the negative electrode layer is not particularly limited, and examples thereof include the solid electrolytes exemplified as the solid electrolyte constituting the solid electrolyte layer described below.
[0098] When the negative electrode layer contains a solid electrolyte, the content of the solid electrolyte may usually be 20 vol. % or more and 60 vol. % or less, particularly 30 vol. % or more and 45 vol. % or less, based on the entire solid electrolyte layer.
[0099] As the sintering aid in the negative electrode layer, the same compounds as the sintering aid in the positive electrode layer can be used. As the conductive assistant in the negative electrode layer, the same compounds as the conductive assistant in the positive electrode layer can be used.
[0100] The thickness of the negative electrode layer is usually 0.1 to 30 μm, and preferably 1 to 20 μm. The thickness of the negative electrode layer is determined by averaging thicknesses measured at any ten points in an SEM image.
[0101] In the negative electrode layer, the porosity is not particularly limited, but is preferably 20% or less, more preferably 15% or less, and further preferably 10% or less.
[0102] The porosity of the negative electrode layer is a value measured in the same manner as the porosity of the positive electrode layer.
[0103] The negative electrode layer is a layer that may be called a “negative electrode active material layer.” The negative electrode layer may have a so-called negative electrode current collector or negative electrode current collector layer.
[0104] (solid electrolyte layer) In the solid-state battery of the present invention, the solid electrolyte layer contains a solid electrolyte.
[0105] The solid electrolyte contained in the solid electrolyte layer is not particularly limited, and may be any solid electrolyte contained in a solid electrolyte layer in the field of solid-state batteries. Such a solid electrolyte may be, for example, an oxide-based electrolyte, and examples thereof include garnet-type oxides (particularly core-shell structure garnet-type oxides) contained in the positive electrode layer, Li 2 ZrO 3 and γ-Li 3 VO 4 and one or more materials selected from a solid electrolyte having a structure and an oxide glass ceramic-based lithium ion conductor. From the viewpoint of further suppressing side reactions during firing at the boundary between the positive electrode layer and the solid electrolyte layer and a decrease in the ion conductivity of the garnet-type oxide, it is preferable that the solid electrolyte layer contains a garnet-type oxide (particularly a core-shell structure garnet-type oxide) contained in the positive electrode layer.
[0106] γ-Li 3 VO4 An example of a solid electrolyte having the structure is a solid electrolyte having an average chemical composition represented by the following general formula (III).
[0107] [ka]
[0108] In formula (III), A is one or more elements selected from the group consisting of Na, K, Mg, Ca, Al, Ga, Zn, Fe, Cr, and Co. B is one or more elements selected from the group consisting of V and P. D is one or more elements selected from the group consisting of Zn, Al, Ga, Si, Ge, Sn, As, Ti, Mo, W, Fe, Cr, and Co. x satisfies 0≦x≦1.0, in particular 0≦x≦0.2. The value of y satisfies 0≦y≦1.0, and in particular 0.20≦y≦0.50. a is the average valence of A. The average valence of A is the value expressed as (n1×a+n2×b+n3×c) / (n1+n2+n3) when, for example, A contains n1 element X with a valence of a+, n2 element Y with a valence of b+, and n3 element Z with a valence of c+. c is the average valence of D. The average valence of D is the same as the average valence of A described above when, for example, n1 element X with a valence a+, n2 element Y with a valence b+, and n3 element Z with a valence c+ are recognized as D.
[0109] γ-Li 3 VO 4 As a specific example of a solid electrolyte having the structure, for example, Li 3.2 (V 0.8 S 0.2 )O 4 , Li 3.5 (V 0.5 Ge 0.5 )O 4 , Li 3.4 (P 0.6 Si0.4)O 4 , Li 3.5 (P0.5 Ge 0.5 )O 4 etc.
[0110] As the oxide glass ceramic-based lithium ion conductor, for example, a phosphate compound containing lithium, aluminum, and titanium as constituent elements (LATP) or a phosphate compound containing lithium, aluminum, and germanium as constituent elements (LAGP) can be used.
[0111] The content of the solid electrolyte in the solid electrolyte layer is not particularly limited, and is, for example, preferably 10 vol% or more and 100 vol% or less, more preferably 20 vol% or more and 100 vol% or less, and even more preferably 30 vol% or more and 100 vol% or less, relative to the entire solid electrolyte layer.
[0112] The solid electrolyte layer may further contain, in addition to the solid electrolyte, for example, a sintering aid. As the sintering aid in the solid electrolyte layer, the same compounds as the sintering aid in the positive electrode layer can be used.
[0113] The content of the sintering aid in the solid electrolyte layer is not particularly limited, and from the viewpoint of further suppressing side reactions during firing and a decrease in the ionic conductivity of the garnet-type oxide, it is preferably from 0 vol. % to 20 vol. %, and more preferably from 1 vol. % to 10 vol. %.
[0114] The thickness of the solid electrolyte layer is usually 0.1 to 30 μm, and preferably 1 to 20 μm from the viewpoint of further suppressing side reactions during firing and a decrease in the ionic conductivity of the garnet-type oxide. The thickness of the solid electrolyte layer is the average value of thicknesses measured at any 10 points in an SEM image.
[0115] In the solid electrolyte layer, the porosity is not particularly limited, and from the viewpoint of further suppressing side reactions during firing and a decrease in the ionic conductivity of the garnet-type oxide, it is preferably 20 vol. % or less, more preferably 15 vol. % or less, and even more preferably 10 vol. % or less.
[0116] The porosity of the solid electrolyte layer is a value measured in the same manner as the porosity of the positive electrode layer.
[0117] [Solid-state battery manufacturing method] The solid-state battery can be manufactured, for example, by the so-called green sheet method, the printing method or a combination of these methods.
[0118] The green sheet method will now be described. First, a paste is prepared by appropriately mixing a core-shell structured garnet-type oxide, a solvent, a binder, etc. with a positive electrode active material. The paste is applied onto a sheet and dried to form a first green sheet for forming a positive electrode layer. The first green sheet may contain other so-called solid electrolytes, conductive additives, and / or sintering additives.
[0119] A paste is prepared by appropriately mixing the negative electrode active material with a solvent, a binder, etc. The paste is applied onto a sheet and dried to form a second green sheet for forming the negative electrode layer. The second green sheet may contain a so-called solid electrolyte, a conductive additive, and / or a sintering additive, etc.
[0120] A paste is prepared by appropriately mixing the solid electrolyte with a solvent, a binder, etc. The paste is applied and dried to prepare a third green sheet for forming the solid electrolyte layer. The third green sheet may contain a sintering aid, etc.
[0121] The solvent for producing the first to third green sheets is not particularly limited, and for example, a solvent that can be used in the manufacture of a positive electrode layer, a negative electrode layer, or a solid electrolyte layer in the field of solid state batteries is used. As the solvent, a solvent that can be used with the binder described below is usually used. As such a solvent, for example, alcohol such as 2-propanol is included.
[0122] The binder for producing the first to third green sheets is not particularly limited, and for example, a binder that can be used in the manufacture of a positive electrode layer, a negative electrode layer, or a solid electrolyte layer in the field of solid state batteries is used. Examples of such binders include butyral resin, acrylic resin, etc.
[0123] Next, the first to third green sheets are appropriately laminated to prepare a laminate. The laminate thus prepared may be pressed. A preferred pressing method is a hydrostatic pressing method. Thereafter, the laminate is sintered at, for example, 600 to 800° C. to obtain a solid-state battery.
[0124] The printing method will be explained. The printing method is similar to the green sheet method, except for the following: Prepare ink for each layer having the same composition as the paste for each layer used to obtain the green sheet, except that the amounts of solvent and resin are suitable for use as an ink. · Each layer is printed using ink and laminated to create a laminate.
[0125] The present invention will be described in more detail below based on specific examples. However, the present invention is not limited to the following examples and can be modified as appropriate within the scope of the present invention. EXAMPLES
[0126] <Examples 1 to 7> [Preparation of core-shell garnet-type oxides] (Production of core particles) As the core particles, a garnet-type oxide powder was produced as follows. The raw material is lithium hydroxide monohydrate (LiOH·H 2 O, lanthanum hydroxide La(OH) 3 , Zirconium oxide ZrO 2 , Tantalum oxide Ta 2 O 5 , Bismuth oxide Bi 2O 3 was used. Each raw material was weighed to have the chemical composition shown in Table 1, water was added, and the raw materials were mixed in a 100 ml polyethylene pot by rotating it on a pot rack at 150 rpm for 16 hours. 2 Considering the Li deficiency during sintering, O was charged in an amount 3 wt% in excess of the target composition. The resulting slurry was evaporated and dried, and then calcined at 900°C for 5 hours to obtain the target phase. A mixed solvent of toluene and acetone was added to the calcined powder obtained, and the mixture was ground in a planetary ball mill for 6 hours. The crushed powder was dried to obtain a garnet-type oxide powder. XRD measurement of the powder confirmed that a garnet-type oxide was obtained. ICP measurement confirmed that the powder had no composition deviation. The average particle size of the core particles was 150 nm. In each example, the primary particle size of the material was not changed, and the structure and composition were controlled by the molar ratio of the raw materials and the firing time.
[0127] (Production of powder with core particles coated with a shell layer) A powder in which core particles were coated with a garnet-type oxide as a shell layer was produced as follows. The raw material is lithium nitrate LiNO 3 , lanthanum nitrate hexahydrate La(NO 3 ) 3 6H 2 O, Bismuth nitrate pentahydrate Bi(NO 3 ) 3 5H 2 O, Zirconium(IV) isopropoxide Zr(OC 3 H 7 ) 4 , Tantalum(V) ethoxide Ta(OC 2 H 5 ) 5 ethyl acetoacetate was used. Each raw material was weighed out so as to have the chemical composition shown in Table 1. Ethyl acetoacetate was weighed out so as to have a molar amount four times that of each alkoxide. First, each alkoxide and ethyl acetoacetate were placed in a glass container and stirred for 30 minutes using a stirrer piece (Solution A). Next, each nitrate and 2-methoxyethanol were placed in a glass container and the nitrate was dissolved (Solution B). Solution A was added dropwise to Solution B to prepare a uniform solution C. After mixing the designated core particles with Solution C, the mixture was mixed for 5 hours using a stirrer piece, and then the solvent was evaporated at 100°C. The obtained dried powder was heat-treated at 700°C for 5 hours to obtain a core-shell structured garnet-type oxide powder having a shell layer on the core particle. In addition, only solution C was dried and then heat-treated at 700°C for 5 hours to obtain a shell layer powder. XRD measurement of the shell layer powder confirmed that a simple garnet-type oxide was obtained. Furthermore, ICP measurement confirmed that there was no composition deviation in the shell layer of the powder. The thickness of the shell layer was 20 to 50 nm. In each example, the primary particle size of the material was not changed, and the structure and composition were controlled by the molar ratio of the raw materials and the firing time.
[0128] [Production of positive electrode active material] The positive electrode active material was prepared as follows. The raw material is lithium hydroxide monohydrate Li 2 CO 3 , Cobalt oxide Co 3 O 4 , Manganese oxide MnO 2 , nickel oxide NiO to Li(Co 0.8 Ni 0.1 Mn 0.1 )O 2 The raw materials were weighed out so as to have the chemical composition, water was added, and the raw materials were mixed by sealing in a 100 ml polyethylene polypot and rotating on a pot rack at 150 rpm for 16 hours. The target phase was then obtained by calcining at 800°C for 5 hours. The average particle size of the positive electrode active material particles after calcination was 5 μm. From the XRD measurement of the above powder, it was confirmed that a single phase of a layered rock salt structure (ICDD card No. 01-070-2685) was obtained. From the ICP measurement, it was confirmed that the above powder had no composition deviation.
[0129] [Production of sintering aids] Lithium hydroxide monohydrate LiOH·H2O, boron oxide B 2 O 3 The starting materials were sintered with a chemical composition of Li 4 B 2 O 5 The mixture was weighed appropriately so that the total weight was adjusted to 100 parts by weight, mixed thoroughly in a mortar, and then calcined at 650° C. for 5 hours.
[0130] [Manufacturing of cathode half cells] First, the core-shell structure garnet-type oxide, the positive electrode active material powder, and the sintering aid powder were weighed out in a volume ratio of 49:50:1, respectively, and mixed with alcohol and a binder to prepare a positive electrode layer slurry. The slurry was then applied onto a sheet and dried to form a first green sheet for constituting the positive electrode layer. In addition, a core-shell structure garnet-type oxide similar to the core-shell structure garnet-type oxide contained in the first green sheet was kneaded with alcohol and a binder to prepare a solid electrolyte layer slurry, and the slurry was dried to form a second green sheet for forming the solid electrolyte layer. A laminate was produced by appropriately stacking the first and second green sheets. The produced laminate was pressed by a hydrostatic press method and appropriately cut to obtain a laminate of a positive electrode layer / solid electrolyte layer. After removing the binder at 400°C, the laminate was pressure-sintered at 800°C for 60 minutes under a pressure of 100 MPa to produce a co-fired body of a positive electrode layer / solid electrolyte layer. After sintering, the thickness of the positive electrode layer was 15 μm, and the thickness of the solid electrolyte layer was about 200 μm. Then, metallic Li was attached to the surface of the solid electrolyte layer opposite the positive electrode layer as a counter electrode and reference electrode, and the resultant was sealed in a 2032-type coin cell to obtain a solid-state battery.
[0131] [Evaluation 1: First-time use rate calculation method] The prepared positive electrode half cell was charged at a current density corresponding to 25°C and 0.05C by a constant current charge / discharge test until the upper limit voltage of 4.2V (vs. Li / Li+) was reached. Then, it was discharged at a current density corresponding to 25°C and 0.05C until the lower limit voltage of 3.0V (vs. Li / Li+) was reached. The initial discharge capacity was calculated by dividing the amount of electricity at the time of the initial discharge obtained from the constant current charge / discharge test by the weight of the positive electrode active material. The initial utilization rate was calculated by dividing the initial discharge capacity by the theoretical capacity (150mAh / g) at the operating potential of the active material used, and was judged according to the following criteria. ◎◎:85%≦First-time usage rate (best); ◎: 70%≦first-time usage rate<85% (excellent); ○;65%≦initial utilization rate<70% (good); △;60%≦initial utilization rate<65% (acceptable) (no practical problems); ×: Initial utilization rate <60% (not acceptable) (problems in practical use).
[0132] [Evaluation 2: Calculation method for utilization rate at 1C discharge] The prepared positive electrode half cell was charged at 25°C and a current density equivalent to 0.05C by a constant current charge / discharge test until it reached an upper limit voltage of 4.2V (vs. Li / Li+). It was then discharged at 25°C and a current density equivalent to 1C until it reached a lower limit voltage of 1.5V (vs. Li / Li+). The discharge capacity at 1C discharge was calculated by dividing the amount of electricity at 1C discharge obtained from the constant current charge / discharge test by the weight of the positive electrode active material. The utilization rate at 1C discharge was calculated by dividing the initial discharge capacity by the theoretical capacity at the operating potential of the active material used (150mAh / g) and was judged according to the following criteria. ◎◎: Utilization rate at discharge of 70%≦1C (best); ◎: Utilization rate at 60%≦1C discharge <70% (excellent); ○; Utilization rate at discharge of 56%≦1C<60% (good); △; 50%≦1C discharge utilization rate<56% (acceptable) (no practical problems); ×: Utilization rate at 1C discharge < 50% (not acceptable) (problems in practical use).
[0133] [Overall Judgment] A comprehensive judgment was made based on all the judgment results (judgment results of ratings 1 and 2). ◎◎: All judgment results were ◎◎. ⊚: Of all the evaluation results, ⊚ was the lowest evaluation result. ○: Of all the evaluation results, the lowest evaluation result was ○. △: Of all the evaluation results, the lowest evaluation result was △. ×: Of all the evaluation results, the lowest evaluation result was ×.
[0134] <Comparative Examples 1 to 3> A positive electrode half-cell was produced and evaluated in the same manner as in Example 1, except that a non-core-shell structured garnet-type oxide produced by the following method was used instead of the core-shell structured garnet-type oxide. The chemical composition of the solid electrolyte used in the solid electrolyte layer of the positive electrode half-cell was Li 6.5 La 3 (Zr 1.5 Ta 0.4 Bi 0.1 )O 12 It was decided.
[0135] [Preparation of non-core-shell garnet-type oxides] A non-core-shell structured garnet-type oxide was produced in the same manner as in the production method of the core particles in Example 1, except that each raw material was weighed so as to obtain the chemical composition shown in Table 1. The average grain size of the non-core-shell garnet-type oxide was 150 nm. In each comparative example, the primary particle size of the material was not changed, and the structure and composition were controlled by the molar ratio of the raw materials and the firing time.
[0136] <Garnet-type crystal structure> The garnet-type crystal structure was confirmed by X-ray diffraction (XRD measurement) by obtaining an X-ray diffraction pattern that could be assigned to a crystal structure similar to that of the garnet type (ICDD Card No. 00-045-0109).
[0137] <Layered rock salt crystal structure> The layered rock-salt crystal structure was confirmed by X-ray diffraction (XRD measurement) which gave an X-ray diffraction pattern that could be assigned to a layered rock-salt crystal structure (ICDD Card No. 01-070-2685).
[0138] <Chemical composition of core particles and shell layer> The measurements were performed by EDX composition analysis using TEM-EDX (energy dispersive X-ray spectroscopy).
[0139] <Measurement of p1 near the interface and p2 inside the particle> The positive electrode layer of the positive electrode half cell was cut in two arbitrary directions by FIB processing, and five arbitrary positive electrode active material particles were focused on in each of the cross sections (TEM cross section view) (a total of 10 positive electrode active material particles). Next, for each positive electrode active material particle 1, the molar ratio of elements other than Li was obtained by TEM-EDX point analysis at 10 arbitrary points in the interface vicinity 23 of the adjacent garnet-type oxide 2. From the obtained molar ratio of the constituent elements, the average p1 value of the interface vicinity 23 was obtained using formula (I). Furthermore, for each positive electrode active material particle 1, the chemical composition was obtained by TEM-EDX point analysis at 10 arbitrary points in the particle interior 22 of the adjacent garnet-type oxide 2, and the average p2 value of the particle interior 22 was obtained. The chemical composition shown in Table 2 was calculated by dividing the element ratio obtained by EDX by B I +B II The absolute values of each constituent element were calculated with β = 3 (β = 3) and α = 7. Since oxygen cannot be quantified, it was calculated as a calculated value taking into account the overall charge guarantee.
[0140] [Table 1]
[0141] [Table 2]
[0142] [Table 3]
[0143] From a comparison between Comparative Example 1 and Examples 1 to 7, it was found that by increasing p1 near the interface (reducing the amount of Li) while maintaining p2 inside the particle at a relatively low value, it is possible to improve the utilization rate during 1C discharge while maintaining a high initial utilization rate. This is believed to be due to the fact that increasing p1 near the interface suppresses side reactions with the positive electrode active material, and maintaining p2 inside the particle at a relatively low value increases the ionic conductivity of the solid electrolyte.
[0144] From a comparison between Example 1 and Example 7, D II It was found that the inclusion of Bi further improved the initial utilization rate and the utilization rate during 1 C discharge. This is believed to be because the increased amount of Bi in the vicinity of the interface improves the sintering of the garnet-type oxide, increasing the contact area between the positive electrode active material and the garnet-type oxide.
[0145] From Comparative Examples 1 to 3, it can be seen that the utilization rate of the initial active material improves as the Li content of the garnet-type oxide decreases, that is, as p increases. This is believed to be because the side reaction with the positive electrode active material having a layered rock salt structure is suppressed by reducing the Li content of the garnet-type oxide. On the other hand, it was also found that the utilization rate during 1C discharge was low at 21% in Comparative Example 3. This is believed to be because the ionic conductivity of the garnet-type oxide decreases with an increase in the Bi content. Although the garnet-type oxide of Comparative Example 1 has high ionic conductivity, it is believed that the capacity retention rate during 1C discharge is also low because the positive electrode active material is modified by co-firing.
[0146] By comparing Examples 1 to 5 and 6 with Example 7, it is clear that when the interface vicinity portion and the inside of the particle satisfy the following conditions for the general formula (I), an overall evaluation result of "◯" or higher can be achieved: D II contains Bi; The p1 and p2 satisfy the following relationship: 0.5≦p1≦2.0; and 0.3≦p2≦1.0.
[0147] By comparing Examples 1 to 3 with Examples 4 to 7, it is clear that when the interface vicinity portion and the inside of the particle satisfy the following conditions for the general formula (I), an overall evaluation result of "A" or higher can be achieved: D II contains Bi; The p1 and p2 satisfy the following relationship: 0.25≦p1-p2≦1.8 0.7≦p1≦2.0; and 0.3≦p2≦0.7. [Industrial Applicability]
[0148] A solid-state battery including the solid electrolyte ceramic of the present invention can be used in various fields where battery use or power storage is expected. By way of example only, a solid-state battery according to an embodiment of the present invention can be used in the field of electronics packaging. The solid-state battery according to an embodiment of the present invention can also be used in the electrical, information, and communication fields in which mobile devices and the like are used (e.g., electrical and electronic devices fields including small electronic devices such as mobile phones, smartphones, smart watches, notebook computers, digital cameras, activity meters, arm computers, electronic paper, wearable devices, RFID tags, card-type electronic money, and smart watches, or mobile device fields), household and small industrial applications (e.g., power tools, golf carts, household, nursing care, and industrial robots), large industrial applications (e.g., forklifts, elevators, and port cranes), transportation systems (e.g., hybrid cars, electric cars, buses, trains, electrically assisted bicycles, and electric motorcycles), power system applications (e.g., various power generation, road conditioners, smart grids, and general household storage systems), medical applications (medical devices such as earphones and hearing aids), pharmaceutical applications (medical management systems), IoT, and space and deep sea applications (e.g., space probes, submersible research vessels, and the like). [Explanation of symbols]
[0149] 1: Positive electrode active material 2: Garnet-type oxide 21: Edge region of garnet-type oxide particles 22: Internal region of garnet-type oxide particle (inside of particle) 23: The area near the interface between the garnet-type oxide and the positive electrode active material (shaded area) R: The interface between the garnet-type oxide and the positive electrode active material
Claims
1. a positive electrode layer, a negative electrode layer, and a solid electrolyte layer disposed between the positive electrode layer and the negative electrode layer; Equipped with the positive electrode layer contains a positive electrode active material and an oxide having a garnet-type crystal structure, The oxide in the vicinity of the interface with the positive electrode active material and the inside of the oxide particle are represented by the following general formula (I): 【Chemistry 1】 [In formula (I), A is one or more elements capable of forming a solid solution in the Li site of the oxide having a garnet-type crystal structure, and is one or more elements selected from the group consisting of Mg (magnesium), Al (aluminum), Ga (gallium), Sc (scandium) and Fe (iron); B I is one or more elements selected from the group consisting of elements that can take a trivalent valence among elements belonging to Groups 1 to 3 that can take an 8-coordination with oxygen, and includes La (lanthanum); B II is one or more elements selected from the group consisting of elements belonging to Groups 1 to 3 that can be eight-coordinated with oxygen and can have a valence other than trivalent, and is one or more elements selected from the group consisting of Ca (calcium), Sr (strontium), Ba (barium), and Ce (cerium); D I is one or more elements selected from the group consisting of transition elements capable of forming 6-coordination with oxygen and elements capable of forming a tetravalent valence among typical elements belonging to groups 12 to 15, and includes Zr (zirconium); D II is one or more elements selected from the group consisting of transition elements capable of forming 6-coordination with oxygen and elements capable of forming a valence other than tetravalent among typical elements belonging to Groups 12 to 15, and includes one or more elements selected from the group consisting of Bi (bismuth) and Ta (tantalum); α, β, γ, ω, x, y and z are as follows: (Area near the interface) α satisfies 5.0≦α≦8.0; β satisfies 2.5≦β≦3.5; γ satisfies 1.5≦γ≦2.5; ω satisfies 11≦ω≦13; x satisfies 0≦x≦1.0; y satisfies 0≦y≦1.0; z satisfies 0.4≦z≦2.2: (inside the particle) α satisfies 5.0≦α≦8.0; β satisfies 2.5≦β≦3.5; γ satisfies 1.5≦γ≦2.5; ω satisfies 11≦ω≦13; x satisfies 0≦x≦1.0; y satisfies 0≦y≦1.0; z satisfies 0.1≦z≦1.
0. The chemical composition is represented by In the general formula (I), p is calculated by the following formula: p=ax-(3-b)y+(d-4)z [wherein a is the average valence of A; b is the average valence of B II is the average valence of D II is the average valence of If expressed as p in the vicinity of the interface (hereinafter referred to as "p1") is larger than p in the interior of the particle (hereinafter referred to as "p2"); The p1 is a solid-state battery that satisfies the following relational expression: 0.4<p1≦2.
0.
2. The solid-state battery according to claim 1 , wherein p1 and p2 satisfy the following relational expression: 0.1≦p1-p2.
3. The solid-state battery according to claim 1 or 2, wherein p1 and p2 satisfy the following relational expression: 0.1≦p2≦1.
5.
4. The above D II The solid-state battery according to any one of claims 1 to 3, wherein contains Bi.
5. The above D II contains Bi, The solid-state battery according to any one of claims 1 to 4, wherein p1 and p2 satisfy the following relational formula: 0.5≦p1≦2.0; and 0.3≦p2≦1.
0.
6. The above D II contains Bi, The solid-state battery according to any one of claims 1 to 5, wherein p1 and p2 satisfy the following relational formula: 0.25≦p1−p2≦1.8 0.7≦p1≦2.0; and 0.3≦p2≦0.
7.
7. The solid-state battery according to claim 1, wherein in formula (I), x and y are 0 in the vicinity of the interface and inside the particle.
8. The solid-state battery according to any one of claims 1 to 7, wherein the positive electrode active material has a layered rock salt structure.
9. The solid-state battery according to any one of claims 1 to 8, wherein the positive electrode layer and the negative electrode layer are layers capable of absorbing and releasing lithium ions.
10. The solid-state battery according to any one of claims 1 to 9, wherein the solid electrolyte layer is integrally sintered with the positive electrode layer and the negative electrode layer.
Citation Information
Patent Citations
Method for manufacturing sintered compact for all-solid battery
JP2017111884A
Laminate green sheet, all-solid secondary battery and manufacturing method thereof
JP2018206486A
Method for manufacturing electrode active substance coated with oxide electrolyte sintered body, electrode active substance coated with oxide electrolyte sintered body, and sulfide solid battery
JP2019121462A